The Characteristics and Dynamics of Cyanobacteria–Heterotrophic Bacteria Between Two Estuarine Reservoirs – Tropical Versus Sub-Tropical Regions - Xu, Zheng; Te, Shu Harn; He, Yiliang; Gin, Karina Yew-Hoong (Frontiers in Microbiology, 2018)
In this study, Illumina Miseq sequencing technique was employed to explore the characteristics and dynamics of cyanobacteria-heterotrophic bacteria between two estuarine reservoirs in sub-tropical (reservoir A in Shanghai) and tropical (reservoir B in Singapore) regions. The results indicated that significant differences in bacterial community composition were found between two estuarine reservoirs, which influenced by varied environmental variables. The environmental heterogeneity in reservoir A was much higher, which indicated that the composition of bacterial community in reservoir A was more complex. In contrast, reservoir B provided a suitable and temperate water environment conditions for bacterial growth, which resulted in higher community diversity and less co-exclusion correlations. The molecular ecological network indicated that the presence of dominant bacterial community in each of the reservoir were significant different. These differences mainly reflected the responses of bacterial community to the variations of environmental variables. Although Synechococcus was the dominant cyanobacterial species in both reservoirs, it exhibited co-occurrence patterns with different heterotrophic bacteria between reservoirs. In addition, the cyanobacteria-heterotrophic bacteria interaction exhibited highly dynamic variations, which was affected by nutrition and survive space. Also, the co-occurrence of Microcystis and Pseudanabaena found in reservoir B implied that the non N-fixing Microcystis accompanied with N-fixing Pseudanabeana occurrence in freshwater lakes, so as to better meet the demand for nitrogen source.